Método para determinar aumento de la presión intraabdomina (2015)
This work describes the current technique for measuring intra-abdominal pressure and its possible morbidities, which form the basis for the development of different measurement methods based on signals obtained by a pressure sensor in an invasive way in which the device is controlled Wirelessly with two modes of operation and an accelerometer noninvasively noninvasively an electronic device that interacts with a mobile device to perform this same measurement by comparing the potential risk of infection using two different invasive techniques.